TRAINING FOR PREPARATION TO ENTER THE WORLD WORK TO IMPROVE ALUMNI SOFT SKILL DEPARTMENT OF IPS ECONOMIC EDUCATION UIN MATARAM - Sehabuddin, Ahmad; Bahri, Saiful (Indonesian Journal of Devotion and Empowerment, 2019)
The problems that occur in the Department of Social Sciences Education at the Islamic State University of Malang are that a) a lot still has no preparation in the form of soft skills in dealing with the world of work; b) a lumni require soft skills l in the world of work; c ) usually requires knowledge of the performance system both in BUMN, BUMS and other institutions.The method for solving these problems is to provide training in preparation for entering the workforce with discussion, demonstration and practice techniques regarding soft skills needed in the world of work. Preparatory training for entering the workforce is one way to equip and instill soft skills combined with actual facts with college alumni. Embedding soft skills in preparation for entering the workforce will help higher education alumni become competent individuals in their careers. Problem yang terjadi pada Alumni Jurusan Pendidikan IPS Ekonomi Universitas Islam Negeri Mataram yakni a) alumni masih banyak belum memiliki persiapan berupa soft skill dalam menghadapi dunia kerja; b) alumni membutuhkan soft skill dalam menghadapi dunia kerja; c) alumni membutuhkan pengetahuan tentang sistem kinerja baik di instansi BUMN, BUMS dan lembaga lainnya. Metode untuk memecahkan problem tersebut yakni memberikan pelatihan persiapan memasuki dunia kerja dengan teknik diskusi, demonstrasi dan praktek mengenai soft skill yang dibutuhkan dalam dunia kerja. Pelatihan persiapan memasuki dunia kerja merupakan salah satu cara untuk membekali dan menanamkan soft skill yang dipadukan dengan fakta-fakta yang bersifat aktual kepada para alumni perguruan tinggi. Penanaman soft skill pada pelatihan persiapan memasuki dunia kerja akan membantu alumni perguruan tinggi menjadi individu yang kompeten dalam berkarir.